2006
DOI: 10.2215/cjn.00550206
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate Mofetil in Children with Frequently Relapsing Nephrotic Syndrome

Abstract: Children with frequently relapsing nephrotic syndrome (FRNS) often develop adverse effects from prednisone. Attempts to induce long-term remission in such patients have had varying levels of success. In this multicenter, prospective, open-label study, 14 centers enrolled 33 patients with FRNS, all of whom were in remission at the time of entry. Six of the patients were steroid dependent. The patients received mycophenolate mofetil (MMF) 600 mg/m 2 twice daily (maximum 1 g twice daily) for 6 mo. A tapering dosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 17 publications
6
41
0
1
Order By: Relevance
“…Subsequently, numerous reports showed that in patients treated with cyclosporine, changing to MMF allowed a similar control of relapse rate with the benefit of improved glomerular filtration rate and hypertrichosis reversal [6][7][8][9][10]. To date, only five prospective studies of MMF in pediatric relapsing NS are available [14][15][16][17][18]. However, in these studies, patients had different past histories, as some had SDNS but others had frequently relapsing NS [16], a situation not as severe as SDNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, numerous reports showed that in patients treated with cyclosporine, changing to MMF allowed a similar control of relapse rate with the benefit of improved glomerular filtration rate and hypertrichosis reversal [6][7][8][9][10]. To date, only five prospective studies of MMF in pediatric relapsing NS are available [14][15][16][17][18]. However, in these studies, patients had different past histories, as some had SDNS but others had frequently relapsing NS [16], a situation not as severe as SDNS.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies on MMF efficacy in pediatric SDNS are limited [14][15][16][17][18]. Demonstrating a statistically significant effect of a new therapy is difficult in rare diseases, as long duration of the inclusion period may be necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Several small studies with limited statistical power have shown that MMF has steroid-sparing effects and reduces relapse rates in patients with FR-SSNS, albeit with varying efficacy. [11][12][13][14][15][16][17][18] We studied efficacy and safety of MMF in patients with FR-SSNS in comparison with CsA in a prospective randomized multicenter open-label crossover trial.…”
mentioning
confidence: 99%
“…Mycophenolate mofetil (MMF) is an immunosuppressive agent more recently added to the therapeutic armamentarium against steroid resistant (SRNS), frequently relapsing (FRNS) and steroid or cyclosporine dependent nephrotic syndrome (SDNS, CsADNS) (1)(2)(3)(4)(5)(6)(7). It has emerged as a new agent without nephrotoxicity and gonadal toxicity (3).…”
Section: Introductionmentioning
confidence: 99%
“…It has emerged as a new agent without nephrotoxicity and gonadal toxicity (3). The most common side effects are gastrointestinal (GI) complaints (gastritis, nausea, vomiting, dyspepsia, constipation, diarrhea, abdominal distention, abdominal pain), anemia, leukopenia, and a predisposition to infection and malignancies (2,5).…”
Section: Introductionmentioning
confidence: 99%